Analysis of Students' Errors in Solving Problems Involving Algebraic Expressions - Ningsih, Firnawati Adia; Lefrida, Rita; Murdiana, I Nyoman; M, Bakri (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to describe students' errors in solving algebra problems in class VII A of SMP Negeri 3 Dampelas. This research employs a descriptive method with a qualitative approach. Three students from class VII A were selected as research subjects, focusing on conceptual and procedural errors. The identified errors include mistakes in concepts, principles, and facts. Conceptual errors involve misconceptions in the addition of like terms. Principle errors occur when students incorrectly conclude the final answer. Factual errors involve mistakes in writing variables. Procedural errors include general mistakes, arithmetic operation errors, and errors in simplifying algebraic fractions.